2015
DOI: 10.1016/j.ydbio.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Kif18a is specifically required for mitotic progression during germ line development

Abstract: Genome integrity in the developing germ line is strictly required for fecundity. In proliferating somatic cells and in germ cells, there are mitotic checkpoint mechanisms that ensure accurate chromosome segregation and euploidy. There is growing evidence of mitotic cell cycle components that are uniquely required in the germ line to ensure genome integrity. We previously showed that the primary phenotype of germ cell deficient 2 (gcd2) mutant mice is infertility due to germ cell depletion during embryogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 36 publications
14
80
0
Order By: Relevance
“…Those abnormalities trigger apoptosis resulting in germ cell depletion and infertility (Czechanski et al, 2015). Interestingly, Kif18a dysregulation in somatic cells, despite chromosome alignment defects, does not cause neither mitotic arrest nor apoptosis (Czechanski et al, 2015). Such discrepancy confirms the unique function of Kif18a in germline development.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Those abnormalities trigger apoptosis resulting in germ cell depletion and infertility (Czechanski et al, 2015). Interestingly, Kif18a dysregulation in somatic cells, despite chromosome alignment defects, does not cause neither mitotic arrest nor apoptosis (Czechanski et al, 2015). Such discrepancy confirms the unique function of Kif18a in germline development.…”
Section: Introductionmentioning
confidence: 78%
“…Since it was reported that Kif18a influences mouse germ cell proliferation (Czechanski et al, 2015;Luo et al, 2018;Zhong et al, 2019), we first investigated such potential effect of human KIF18A on TCam-2 cells, which originates from male germ cells. For that purpose we performed MTS proliferation assay upon KIF18A knockdown, starting at 24 h up to 120 h post transfection.…”
Section: Knockdown Of Kif18a Caused Decreased Tcam-2 Cell Proliferatimentioning
confidence: 99%
See 2 more Smart Citations
“…However, unlike HeLa cells expressing the mutant Kif18A, Kif18A gcd2 mouse embryonic fibroblasts (MEFs) successfully progressed through mitosis, entering anaphase with unaligned chromosomes (Czechanski et al, 2015). One interpretation of this finding is that the absolute positioning of chromosomes at the spindle equator might not be necessary, although it remains to be tested whether sister kinetochores are in fact correctly bi-orientated and that the metaphase plate is simply broader.…”
Section: Coupling Congression With Position-sensing In the Spindlementioning
confidence: 99%